Bronchiolitis and Bronchiolar Disorders - Ravaglia, Claudia; Poletti, Venerino (Seminars in Respiratory and Critical Care Medicine, 2020)
Bronchioles are noncartilaginous small airways with internal diameter of 2 mm or less, located from approximately the eighth generation of purely air conducting airways (membranous bronchioles) down to the terminal bronchioles (the smallest airways without alveoli) and respiratory bronchioles (which communicate directly with alveolar ducts and are in the range of 0.5 mm or less in diameter). Bronchiolar injury, inflammation, and fibrosis may occur in myriad disorders including connective tissue diseases, inflammatory bowel diseases, lung transplant allograft rejection, graft versus host disease in allogeneic stem cell recipients, neuroendocrine cell hyperplasia, infections, drug toxicity (e.g., penicillamine, busulfan), inhalation injury (e.g., cigarette smoke, nylon flock, mineral dusts, hard metals, Sauropus androgynous); idiopathic, common variable immunodeficiency disorder, and a host of other disorders or insults. The spectrum of bronchiolar disorders is wide, ranging from asymptomatic to fatal obliterative bronchiolitis. In this review, we discuss the salient clinical, radiographic, and histological features of these diverse bronchiolar disorders, and discuss a management approach.
Keywords: bronchiolitis; small airways; cellular bronchiolitis; constrictive bronchiolitis; follicular bronchiolitis; lymphocytic bronchiolitis; cryptogenic organizing pneumonia